Paradoxes of Urban Housing Informality in the Developing World. Issue 3 (22nd July 2013) - van, Jean‐Louis
<x xml:space="preserve">Abstract</x> This article addresses a series of paradoxes regarding informal settlements in cities in the developing world and their relation with the legal system. The first paradox regards the penalization of illegal land occupations on the one hand versus the legalization of that same practice on the other. Second, it looks at the relationship between land occupations as systematic violations of property rights, but with the goal of forming new property rights and thus paradoxically supporting private property as a substantive principle. Third, the reasoning behind the fact that the same system that denies legal access to housing for poor sectors simultaneously attempts to incorporate informal settlements in an ad hoc manner through legalization schemes is examined. It is shown that there is a logic to these paradoxes, which, although contradictory from standard legal perspectives, can be accommodated within a theoretical framework that distinguishes an internal normative order operating within informal settlements, from the state legal system, operative outside it. The proposed framework not only settles the paradoxes, but, this article concludes, can also guide attempts to deal with the enormous anticipated growth of informality in the developing world.